(untitled) - Guest, Simon (Redmond, Wash., 2004)
Discover how to build applications that run on both the Microsoft .NET Framework and Java 2 Enterprise Edition (J2EE)—and extend your customer reach and system shelf life. Whether your background is in .NET or J2EE, you’ll learn to implement many of the interoperability technologies available today, including Microsoft, Sun, and third-party compatibility tools. Interoperability expert Simon Guest takes a balanced look at the pros and cons of each cross-platform technology presented, including best practices, workarounds, and examples of interoperability solutions in action. You also get interoperability software on CD—plus a wealth of code you can use in your own solutions
Keywords: Microsoft .net,Java ( computer program language )